#TITLE_ALTERNATIVE# - HAMJEN (NIM : 10208104); Pembimbing : Dr. rer. nat. Bobby Eka Gunara, WIRO
In this paper we consider MaxwellÃ‚Â’s vector potential on Schwarzschild geometry. We choose that solution to be static and satisfying Maxwell vacuum condition. We investigated potential vector component by using identity. We show there are electric and magnetic monopole solutions. Its energy tensor shows physical consitency of this solution as static soliton.